The Case of Dracontius (X. An. 4.8.25) and Spartan Homicide Law (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2023)
The prevailing interpretation of the case of Dracontius (X. An. 4.8.25) has long been that Dracontius was exiled from Sparta for unintentional homicide. This paper argues that that interpretation is incorrect. Xenophon’s description of the event indicates that Dracontius intended to strike his victim. Consequently, comparanda including the laws of Athens, of Antiphon’s Tetralogies, and of Plato’s Laws support the conclusion that Dracontius was treated as an intentional killer. The duration of Dracontius’ exile provides further evidence in favor of this position. Strict liability for homicide at Sparta, of the type familiar from the case of Patroclus (Hom. Il. 23.85-88) and from Homeric and Hesiodic epic generally, is contraindicated by the Spartan concern with oliganthrōpia and the violence of the agōgē. Whether Dracontius’ exile was penal or voluntary thus depends on the penalty for intentional homicidein Spartan law. If that penalty was fixed, then in all probability it was fixed at death, and Dracontius fled of his own accord to avoid that punishment. If, however, the penalty was assessable, then Dracontius either was sentenced to exile or fled voluntarily to avoid a possible sentence of death. These two alternative reconstructions of the Spartan law of intentional homicide in turn determine the reconstruction of the law of unintentional homicide, which will have carried a lesser penalty.
Keywords: sparta; homicide; dracontius; greek law; Xenophon